ELEMEN-ELEMEN KOREOGRAFI DAN REFLEKSI DALAM SAJIAN KARYA TARI TUNJUNG PUTIH - Divany Rico Jhosua; Mamik Widyastuti (Greget, 2021)
Tunjung Putih dance by the choreographer; Divany Rico Jhosua in 2020 is a new traditional art whose dance work creation is motivated by the problem of social discrimination experienced by cross-dressers and cross-gender dancers. The idea of creating this work is the story of Wrahatnala's character while posing as a woman and acting like a sissy. To find out the elements of choreography in Tunjung Putih dance, the author uses the concept presented by Y. Sumandyo Hadi, namely the explanation of the concepts of cultivation through the elaboration of choreographic elements. The result of this study is to know the form of Tunjung Putih dance through the description of 11 elements of choreography in it. Reflection of the creation of Tunjung Putih dance in the form of critical analysis with further research to respondents on issues and responses related to the presentation of this dance work.